2007
DOI: 10.1172/jci32401
|View full text |Cite
|
Sign up to set email alerts
|

Identification of HLA-DR–bound peptides presented by human bronchoalveolar lavage cells in sarcoidosis

Abstract: Sarcoidosis is an inflammatory disease of unknown etiology, most commonly affecting the lungs. Activated CD4 + T cells accumulate in the lungs of individuals with sarcoidosis and are considered to be of central importance for inflammation. We have previously shown that Scandinavian sarcoidosis patients expressing the HLA-DR allele DRB1*0301 are characterized by large accumulations in the lungs of CD4 + T cells expressing the TCR AV2S3 gene segment. This association afforded us a unique opportunity to identify … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
85
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(92 citation statements)
references
References 42 publications
5
85
0
2
Order By: Relevance
“…Literature search yielded a number of T-cell autoantigens that were also detectable in our samples ( Table 2). The table only includes T-cell autoantigens for which reactivity has been experimentally verified in humans, such as vimentin (rheumatoid arthritis, sarcoidosis) 34,35 , ATP synthase (sarcoidosis) 35 , enolase 2 (multiple sclerosis) 36 and heat shock protein 70 (type 1 diabetes mellitus) 37 . For those autoantigens where reactivity against specific epitopes (rather than whole protein) was reported, the epitopes were identical to, or contained within the peptide sequences that we identified in our samples, mostly on DCs.…”
Section: Resultsmentioning
confidence: 99%
“…Literature search yielded a number of T-cell autoantigens that were also detectable in our samples ( Table 2). The table only includes T-cell autoantigens for which reactivity has been experimentally verified in humans, such as vimentin (rheumatoid arthritis, sarcoidosis) 34,35 , ATP synthase (sarcoidosis) 35 , enolase 2 (multiple sclerosis) 36 and heat shock protein 70 (type 1 diabetes mellitus) 37 . For those autoantigens where reactivity against specific epitopes (rather than whole protein) was reported, the epitopes were identical to, or contained within the peptide sequences that we identified in our samples, mostly on DCs.…”
Section: Resultsmentioning
confidence: 99%
“…Two of the peptides (K15 and K20) were matched to HLA class II epitopes reported to be eluted from HLA-DRβ*0404 (K15-C and K20-C) and HLA-DRβ*0301 (K15-D and K20-D; Table 4; Kirschmann et al 1995;Wahlstrom et al 2007). The peptides with either an intensity lower than the double average value of the negative control spots, or did not reach an intensity higher than a twofold increase over the corresponding control, were assessed as none binding (0).…”
Section: Resultsmentioning
confidence: 99%
“…Oshitani et al reported 55 HLA-DR peptides from human intestine samples of 4 controls and 18 patients affected by inflammatory bowel disease (13). More recently, 78 peptides have been reported from a pool of 16 bronchoalveolar lavage samples from patients with sarcoidosis, being the first such study in human autoimmunity, although the nature of the samples was very different (23). Using a different approach, a recent study has shown that most peptides bound to MHC-II from mouse insulinoma cells derive from proteins normally expressed in ␤ cells from normal islets and that some of them are recognized by CD4 ϩ T cells from NOD mice (24).…”
Section: Discussionmentioning
confidence: 99%